2020
DOI: 10.1039/d0cs00452a
|View full text |Cite
|
Sign up to set email alerts
|

Internal catalysis for dynamic covalent chemistry applications and polymer science

Abstract: In this review, we provide a concise analysis of internal catalysis as an attractive design principle to combine chemical robustness with reactivity in dynamic covalent chemistry applications and a material context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
168
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(169 citation statements)
references
References 50 publications
1
168
0
Order By: Relevance
“…This behavior is in adequation with one of the first observations made by Leibler et al about the relationship between the amount of catalyst and the short τ* of vitrimers 6. Moreover, the catalytic effect is more pronounced thanks to the close position of the NR 3 groups regarding the -OH groups, in agreement with the NGP theory recently disclosed by Du Prez et al11 and illustrated in Scheme 1.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…This behavior is in adequation with one of the first observations made by Leibler et al about the relationship between the amount of catalyst and the short τ* of vitrimers 6. Moreover, the catalytic effect is more pronounced thanks to the close position of the NR 3 groups regarding the -OH groups, in agreement with the NGP theory recently disclosed by Du Prez et al11 and illustrated in Scheme 1.…”
supporting
confidence: 91%
“…They were called poly(PEG-DPA-mea 75 /fa 25 ), poly(PEG-DPA-mea 50 /fa 50 ), poly(PEG-DPA-mea 25 /fa 75 ), corresponding to materials where 75%, 50% and 25% of mea was substituted by 75%, 50% and 25% of fa, respectively. NMR revealed that they correspond to materials containing a ratio of N/COO/OH equal to 2/1/1.38, 2/ 1/0.91 or 2/1/0.5, in respect to the order given in the sentence above (Table 1, rows [10][11][12]. The details of the preparation and characterization of all the materials can be found in the ESI (Fig.…”
Section: Effect Of the Structural Features On The Vitrimer Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The dissociable nature of the covalent bonds endows the networked polymers with chemical recyclability 1–5 . The re‐workability and self‐repairing ability of polymer networks are also enabled using dynamic covalent bonds 6–10 . Equilibrium polymerization of heterocyclic monomers such as cyclic carbonates and bicycloorthoesters is also a useful tool for the construction of chemical recycling systems 11,12 …”
Section: Introductionmentioning
confidence: 99%